Brainstem atrophy in dementia with Lewy bodies compared with progressive supranuclear palsy and Parkinson’s disease on MRI - Sebastian Johannes Müller; Eya Khadhraoui; Niels Hansen; Ala Jamous; Philip Langer; Jens Wiltfang; Christian Heiner Riedel; Caroline Bouter; Christoph van Riesen; Fabian Maass; Michael Bartl; Claudia Lange; et al. (BMC Neurology, 2023)
Abstract Background Although Dementia with Lewy bodies (DLB) is the second most common form of dementia in elderly patients, it remains underdiagnosed compared with Alzheimer's (AD) and Parkinson's diseases (PD). This may be explained by overlapping clinical symptoms, e.g. Parkinsonism. While current MRI research focuses primarily on atrophy patterns of the frontal and temporal lobes, we focus on brainstem characteristics of DLB. In particular, we focused on brainstem atrophy patterns distinguishing DLB from Progressive Supranuclear Palsy (PSP) and PD based as the most common differential diagnoses. Methods We identified patients diagnosed with DLB, PD, PSP, and a control group (CTRL) in our psychiatric and neurological archives. All patients with competing diagnoses and without a high-quality T1 MPRAGE 3D dataset were excluded. We assessed atrophy patterns in all patients (1) manually and (2) using FastSurfer’s segmentation algorithm in combination with FreeSurfer’s brainstem volumetric calculations. We compared classical measurement methods and ratios with automated volumetric approaches. Results One hundred two patients were enrolled and evaluated in this study. Patients with DLB (n = 37) showed on average less atrophy of the brainstem than patients with PSP (n = 21), but a significantly more pronounced atrophy than patients with PD (n = 36) and the control group (CTRL, n = 8). The mean measured sagittal diameters of the midbrain were 8.17 ± 1.06 mm (mean ± standard deviation) for PSP, 9.45 ± 0.95 mm for DLB, 10.37 ± 0.99 mm for PD and 10.74 ± 0.70 for CTRL. The mean measured areas of the midbrain were 81 ± 18 mm2 for PSP, 105 ± 17 mm2 for DLB, 130 ± 26 mm2 for PD and 135 ± 23 mm2 for CTRL. The mean segmented volumes of the midbrain were 5595 ± 680 mm3 for PSP, 6051 ± 566 mm3 for DLB, 6646 ± 802 mm3 for PD and 6882 ± 844 mm3 for CTRL. The calculated midbrain pons ratios did not show superiority over the absolute measurements of the midbrain for distinguishing PSP from DLB. Because of the relatively uniform atrophy throughout the brainstem, the ratios were not suitable for distinguishing DLB from PD. Conclusions DLB patients exhibit homogenous atrophy of the brainstem and can be distinguished from patients with PSP and PD by both manual measurement methods and automated volume segmentation using absolute values or ratios.